A (−)‐norephedrine‐based molecularly imprinted polymer for the solid‐phase extraction of psychoactive phenylpropylamino alkaloids from Khat (Catha edulis Vahl. Endl.) chewing leaves. (1st December 2015) - Atlabachew, Minaleshewa; Torto, Nelson; Chandravanshi, Bhagwan Singh; Redi‐Abshiro, Mesfin; Chigome, Samuel; Mothibedi, Kediemetse; Combrinck, Sandra
Abstract: A molecularly imprinted polymer (MIP) was prepared using (−)‐norephedrine as the template, methacrylic acid as the functional monomer, ethylene glycol dimethacrylate as the cross‐linker and chloroform as the porogen. The MIP was used as a selective sorbent in the molecularly imprinted solid‐phase extraction (MIP‐SPE) of the psychoactive phenylpropylamino alkaloids, norephedrine and its analogs, cathinone and cathine, from Khat ( Catha edulis Vahl. Endl.) leaf extracts prior to HPLC‐DAD analysis. The MIP was able to selectively extract the alkaloids from the aqueous extracts of Khat. Loading, washing and elution of the alkaloids bound to the MIP were evaluated under different conditions. The clean baseline of the Khat extract obtained after MIP‐SPE confirmed that a selective and efficient sample clean‐up was achieved. Good recoveries (90.0–107%) and precision (RSDs 2.3–3.2%) were obtained in the validation of the MIP‐SPE‐HPLC procedure. The content of the three alkaloids in Khat samples determined after treatment with MIP‐SPE and a commercial Isolute C18 (EC) SPE cartridge were in good agreement. These findings indicate that MIP‐SPE is a reliable method that can be used for sample pre‐treatment for the determination of Khat alkaloids in plant extracts or similar matrices and could be applicable in pharmaceutical, forensic and biomedical laboratories. Copyright © 2015 John Wiley & Sons, Ltd.